ASSESSMENT OF GENETIC STRUCTURE OF CLARIAS GARIEPINUS, BURCHELL, 1822 POPULATION IN ASEJIRE LAKE (2014)
Wild brood-stock is a major genetic reservoir for sustainable culture of Clarias gariepinus. This has been observed to be declining in major freshwater dams in Nigeria. There is inadequate information on factors responsible for this decline and their effects on genetic structuring of the fish resources in these dams. This study therefore investigated genetic structure of C. gariepinus in relation to environmental condition of Asejire Dam. The Dam was spatially divided into Oyo State (OYS) and Osun State (OSS) strata. Thirty-eight sites were randomly selected, nineteen sites from each stratum. Water Quality Parameters (WQP) were sampled bimonthly in wet and dry seasons for 24months. The WQP selected were temperature, Dissolved Oxygen (DO), Total Hardness (TH) and Total Alkalinity (TA). Catchment area was assessed for indices of threat to environmental condition; Watershed Forest Degradation (WFD), frequencies of Partial Dam Gate Opening (PDGO) and Complete Dam Gate Opening (CDGO). Clarias gariepinus catches from fishermen’s landings were used to study genetic structure by examining variability in phenotypes and genotypes. Phenotypic data obtained were regrouped to subgroups of sex, size, and grades of Possession of Anteriorly Serrated Pectoral Spine (PASPS). Regrouped cases that had significantly different subgroups’ phenotypes were further screened for presence of Private Allele (PA), polymorphism of protein, DNA bands and genetic distance using standard procedures. Data were analysed using descriptive statistics, student’s t-test and cluster analysis. Seasonal variations in WQP for wet and dry seasons were 27.4±3.2 and 30.0±2.5οC (temperature); 6.1±1.8 and 5.0±2.1 mg/l (DO); 51.7±27.1 and 52.0±38.0 mg/l (TH); 55.3±43.7 and 134.00±89.5 mg/l (TA) respectively. The WQP values of 28.6±2.7 and 28.7±4.0οC (temperature), 6.1±1.2 and 6.5±1.5 mg/l (DO), 52.7±6.2 and 51.7±38.3 mg/l (TH), 146.7±58.3 and 91.0±43.4 mg/l (TA) were recorded at OYS and OSS respectively. There was 8.5% reduction in catchment area while 66.0% wetland areas were under human activities. The PDGO for wet and dry seasons were 30 and 8 times respectively. Wet and dry seasons’ CDGO occurred 2 times. Thirty-seven Clarias gariepinus were identified from 1,392 fish catches. Dorsal ray counts ranged from 63 to 71. Dorsal ray counts were significantly different (F=3.51, p=0.008) between size subgroups. Anal fin lengths in PASPS subgroups were between 39.0 and 44.0% of standard lengths. These values were significantly different (F=4.25, p=0.001) among the subgroups. Polymorphism and PA of protein markers occurred in PASPS at 14.7kDa. The DNA analysis revealed 82.5% polymorphic sites from 746 bands. The PASPS subgroups genotypes formed two different clusters and had within cluster variability at 62.0% CV. Watershed forest degradation indices: catchment areas’ reduction and increase in wetland areas under human activities in addition to frequency of opening of the dams’ gate were the main threats to Clarias gariepinus population in Asejire Dam. Genetic structure indicated presence of strains with high variability in Clarias gariepinus